2018
DOI: 10.1002/ecy.2434
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed canopy nitrogen correlates with nitrous oxide emissions in a lowland tropical rainforest

Abstract: Tropical forests exhibit significant heterogeneity in plant functional and chemical traits that may contribute to spatial patterns of key soil biogeochemical processes, such as carbon storage and greenhouse gas emissions. Although tropical forests are the largest ecosystem source of nitrous oxide (N O), drivers of spatial patterns within forests are poorly resolved. Here, we show that local variation in canopy foliar N, mapped by remote-sensing image spectroscopy, correlates with patterns of soil N O emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…For example, the decline in litter mass : N during secondary succession is consistent with the notion that plants may resorb less N prior to abscission late in succession than early in succession, before N capital has been restored by N 2 fixation (Batterman et al 2013). Plant traits such as litter chemistry can shape local biogeochemical cycling rates by influencing processes including decomposition and mineralization (Osborne et al 2017, Soper et al 2018. Increasing foliar d 15 N during secondary succession could be the product of numerous processes, but is consistent with fractionation of the soil N pool associated with increased soil N gas loss (Houlton et al 2006), as we observed, and with declining symbiotic N 2 fixation inputs during secondary succession (Barron et al 2011, Batterman et al 2013, Sullivan et al 2014) that may be associated with down-regulation of N 2 fixation in facultative species with increasing soil N availability.…”
Section: Soil Ordersupporting
confidence: 65%
See 3 more Smart Citations
“…For example, the decline in litter mass : N during secondary succession is consistent with the notion that plants may resorb less N prior to abscission late in succession than early in succession, before N capital has been restored by N 2 fixation (Batterman et al 2013). Plant traits such as litter chemistry can shape local biogeochemical cycling rates by influencing processes including decomposition and mineralization (Osborne et al 2017, Soper et al 2018. Increasing foliar d 15 N during secondary succession could be the product of numerous processes, but is consistent with fractionation of the soil N pool associated with increased soil N gas loss (Houlton et al 2006), as we observed, and with declining symbiotic N 2 fixation inputs during secondary succession (Barron et al 2011, Batterman et al 2013, Sullivan et al 2014) that may be associated with down-regulation of N 2 fixation in facultative species with increasing soil N availability.…”
Section: Soil Ordersupporting
confidence: 65%
“…A recent model analysis demonstrated that the resilience of tropical forest to climate-change type disturbance may depend on plant trait diversity (Sakschewski et al 2016), which could reflect the influence of plant traits on biogeochemical cycling (Soper et al 2018). A recent model analysis demonstrated that the resilience of tropical forest to climate-change type disturbance may depend on plant trait diversity (Sakschewski et al 2016), which could reflect the influence of plant traits on biogeochemical cycling (Soper et al 2018).…”
Section: Soil Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…F I G U R E 4 Methodological and interdisciplinary approaches needed to explore the plant functional traits that determine N-cycling and NUE in intensive agroecosystems For example, a combination of remote sensing (e.g. Unmanned Aerial Vehicles) and imaging spectroscopy enables for non-invasive assessment of plant traits such as LNC (Soper et al, 2018;van der Meij, Kooistra, Suomalainen, Barel, & De Deyn, 2017), essential for estimation of NUE at enhanced spatial-temporal resolutions. Process-based biogeochemical models (e.g.…”
Section: Field Regional and Global Scalesmentioning
confidence: 99%